2018
DOI: 10.1007/s11250-018-1530-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and indicators of reduced welfare of grazing dairy cows from selected smallholder dairy farms in Midlands Province, Zimbabwe

Abstract: Zimbabwe's smallholder dairying faces many challenges that affect the welfare of dairy cows; however, the status of this welfare has not yet been determined. A cross-sectional study was conducted in Midlands Province on 41 active smallholder dairy farms with 86 cows in winter and summer to determine the risk factors and indicators to impaired cow welfare. These objectives were achieved using farmer questionnaires and direct observations. Eleven percent of the observed cows were severely lame in summer while on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In a study by Moreira et al (2019), cow hygiene and longer hours spent in corrals were two risk factors for both lameness and digital dermatitis. Matore et al (2018) found that breed (Holstein-Friesian crosses), season (summer rainy season), lack of shade and low dipping frequency statistically significantly increased lameness prevalence in smallholder dairy farms in Zimbabwe. Genetic factors have a significant influence on foot and leg traits in dairy cattle (van Amstel and Shearer, 2006).…”
Section: Introductionmentioning
confidence: 92%
“…In a study by Moreira et al (2019), cow hygiene and longer hours spent in corrals were two risk factors for both lameness and digital dermatitis. Matore et al (2018) found that breed (Holstein-Friesian crosses), season (summer rainy season), lack of shade and low dipping frequency statistically significantly increased lameness prevalence in smallholder dairy farms in Zimbabwe. Genetic factors have a significant influence on foot and leg traits in dairy cattle (van Amstel and Shearer, 2006).…”
Section: Introductionmentioning
confidence: 92%
“…However, most of the studies on lameness and reproductive performance have been carried out on dairy breeds such as Holstein and Brown Swiss, with only some including a small proportion of Jerseys and crossbreeds in the sampled population [ 26 , 27 , 34 , 35 , 36 , 37 , 38 ]. Regarding extrinsic factors, humid and hot environments have been demonstrated to increase the prevalence of lameness in dairy cows [ 37 , 39 , 40 , 41 ] due to those conditions that can not only soften and damage hooves [ 42 ], but also trigger normal adaptive changes, such as an increase in total locomotor activity and a reduction in lying behaviour to minimise exposure to hot–humid surfaces [ 43 ]. Jerseys have been demonstrated to be much more successful in adapting to tropical conditions and their associated heat stress in comparison to other dairy breeds, such as Holstein [ 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%